A Proposed Model and Framework for Developing a Curriculum for Indigenous Learners with Disabilities (American Journal of Youth and Women Empowerment, 2022)
The experiences of indigenous person with disabilities at the intersection of being an indigenous person and being a person with disability can be described as a case of double discrimination. Special Education, which is one of the measures stated in the United Convention on the Rights of Persons with Disabilities to eradicate disability discrimination as well as to promote full and effective participation in society, is still an area studies which has not been investigated in detail from an indigenous perspective. In the Philippines, for example, even though inclusion is an embodied philosophy and policy in its Enhanced Basic Education Curriculum, it does not clearly provide for a guide for implementing special education services to indigenous learners with disabilities. Thus, in this paper, I explored into the gaps of disability from an Indigenous perspective and the primary Philippine policies on disability education and Indigenous Peoples Education. These analyses were used to conceptualizing a proposed model and framework for developing a curriculum for Indigenous Learners with Disabilities.